2011
DOI: 10.1002/fut.20541
|View full text |Cite
|
Sign up to set email alerts
|

Commonality in trading activity and futures‐cash basis: Evidence from the Taiwan futures and stock markets

Abstract: This study examines commonality in trading activity by various types of institutional investors across futures and stock markets, and the dynamic relationship between the common factors in trading activity and the futures-cash basis. The empirical results provide evidence of commonality in trading activity by various types of institutional investors across futures and stock markets. Additionally, this study finds that the first principal component of trading activity is most closely related to the futures trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…The results thereby suggest that liquidity plays an important role in moving markets toward an efficient outcome. Same findings have been documented in the international markets as well (e.g., Lee, Chien and Liao, 2012;Kadapakkam and Kumar, 2013).…”
Section: Topic 2: Market Efficiencysupporting
confidence: 77%
See 1 more Smart Citation
“…The results thereby suggest that liquidity plays an important role in moving markets toward an efficient outcome. Same findings have been documented in the international markets as well (e.g., Lee, Chien and Liao, 2012;Kadapakkam and Kumar, 2013).…”
Section: Topic 2: Market Efficiencysupporting
confidence: 77%
“…1 This twoway relation also exists in the international markets (e.g., Lee, Chien and Liao, 2012;Kadapakkam and Kumar, 2013).…”
Section: On the Relation Between Liquidity And The Futures-cash Basismentioning
confidence: 99%
“…However, the obtained results are not always consistent (Terza et al, 2008) [31]. We believe that the basis value lagging by two phases can be introduced in the right side of the regression model (12) to serve as the instrumental variable. The quantile regression based on the instrumental variable can relatively effectively reduce the endogeneity of the model.…”
Section: Robustness Analysis Of the Endogeneity Caused By Thementioning
confidence: 79%
“…Fourthly, irrational noise trade is likely to result in the continuous rise of the market price and the theoretical price. From the perspective of trading behavior of different types of investors, Lee et al (2012) [12] found from empirical research that irrational behaviors of investors in different structures have different influences on the basis. Therefore, the effects of the investor sentiment on the basis can be probably impacted by different investor structures: institutional investors in the market are basically more rational in terms of the investment (Daniel et al, 1997) [13], while individual investors are more likely to behave irrationally while making their investment decisions (Odean, 1998) [14].…”
Section: Hypotheses To Be Tested and Research Designmentioning
confidence: 99%
“…1 This two-way relation also exists in the international markets (e.g., Lee, Chien, and Liao, 2012;Kadapakkam and Kumar, 2013).…”
Section: Introductionmentioning
confidence: 99%